2007
DOI: 10.1007/s00259-006-0262-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MDMA on blood glucose levels and brain glucose metabolism

Abstract: Purpose This study was designed to assess changes in glucose metabolism in rats administered single or repeated doses of MDMA. Methods Two different experiments were performed: (1) A single-dose study with four groups receiving 20 mg/kg, 40 mg/kg, saline or heat, and (2) a repeated-dose study with two groups receiving three doses, at intervals of 2 h, of 5 mg/kg or saline. Rats were imaged using a dedicated small-animal PET scanner 1 h after single-dose administration or 7 days after repeated doses. Glucose me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Results from studies on the effects of MDMA on cerebral glucose metabolism have not been consistent. Although Quate et al (2004) have reported that MDMA acutely increases local cerebral glucose utilization in many brain regions, the finding has not been replicated by others (Wilkerson and London, 1989; Soto-Montenegro et al, 2007). Thus, it is unclear whether the MDMA-induced increase in extracellular glucose is reflective of an increase in neuronal energy demand.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Results from studies on the effects of MDMA on cerebral glucose metabolism have not been consistent. Although Quate et al (2004) have reported that MDMA acutely increases local cerebral glucose utilization in many brain regions, the finding has not been replicated by others (Wilkerson and London, 1989; Soto-Montenegro et al, 2007). Thus, it is unclear whether the MDMA-induced increase in extracellular glucose is reflective of an increase in neuronal energy demand.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies on the effect of MDMA on peripheral glucose have provided inconsistent results. Soto-Montenegro et al (2007) demonstrated that MDMA produces a 35% reduction in blood glucose, whereas Gramsbergen and Cumming (2007) and Banks et al (2009) have reported that relatively large doses of MDMA administered i.v. result in a transient increase in blood glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown previously that acute MDMA results in increased cerebral glucose levels in the adult rat [18,22,23,45] as well as in the periphery [23], although decreased cerebral glucose utilization is evident over time in MDMA-treated rats [22]. On the contrary, in Dark Agouti female rats, which are poor metabolizers of MDMA, exposure results in decreased blood glucose levels [60], implying that the pharmacology and metabolism of MDMA itself may play a role in glucose utilization. These data do not, however, indicate why adolescent rats are resistant to drug-induced hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, other investigators have failed to confirm an effect of MDMA to increase blood glucose. Soto-Montenegro et al (2007) have reported that MDMA actually decreases peripheral glucose and Darvesh et al (2002) failed to find any significant effect of MDMA on blood glucose at a dose that elevated brain extracellular concentrations of glucose. Thus, the source of the increased extracellular glucose in brain following MDMA remains to be resolved, as well as its relationship to a potential increase in cerebral blood flow and/or tissue glucose utilization.…”
Section: Energy Substratesmentioning
confidence: 99%